Access to azonanes via Pd-catalyzed decarboxylative [5 + 4] cycloaddition with exclusive regioselectivity. Issue 24 (11th November 2021) - Liu, Yin; He, Yicheng; Liu, Yang; Wei, Kun; Guo, Wusheng
Abstract : An efficient approach for the synthesis of azonanes via Pd-catalyzed decarboxylative [5 + 4] cycloaddition has been developed. The reactions feature wide functional group tolerance with exclusive regioselectivity. Abstract : A highly efficient approach for the synthesis of azonanes via Pd-catalyzed decarboxylative [5 + 4] cycloaddition has been developed. This procedure utilizes methylene cyclic carbonates as a C5-dipole and 1-azadiene as a C4-synthon. The reactions could be performed at room temperature. The protocol features wide functional group tolerance with exclusive regioselectivity and generates CO2 as the only byproduct.